Institutional Trust 2012 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Sifo (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Sifo and involved 1017 individuals who answered a web survey between February 8 and 14, 2012. The survey comprised 43 institutions/companies/media companies and political parties. The 2012 survey also included questions about to what extent some twenty professions as well as twenty individuals involved in Swedish media were trusted.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2012 genomfördes av TNS Sifo och omfattade 1017 personer som besvarade en nätenkät. Studien genomfördes 8/2 - 14/2 2012 och innefattade 43 institutioner/företag/medier/partier. I 2012 års undersökning ingick även frågor om förtroendet för ett tjugotal yrkesgrupper samt frågor om förtroendet för tjugo namngivna personer verksamma inom svenska medier. Därtill ingick en specialmätning av Estelle-effekten på förtroendet för kungahuset.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2012
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper